Hypervalent iodine-mediated Ritter-type amidation of terminal alkenes: The synthesis of isoxazoline and pyrazoline cores - Park, Sang Won; Kim, Soong-Hyun; Song, Jaeyoung; Park, Ga Young; Kim, Darong; Nam, Tae-Gyu; Hong, Ki Bum (Beilstein Journal of Organic Chemistry, 2018)
Hypervalent iodine-mediated olefin functionalization provides a rapid gateway towards accessing both various heterocyclic cores and functional groups. In this regard, we have developed a Ritter-type alkene functionalization utilizing a PhI(OAc)2 ((diacetoxyiodo)benzene, PIDA)/Lewis acid combination in order to access isoxazoline and pyrazoline cores. Based on allyl ketone oximes and allyl ketone tosylhydrazones, we have developed an alkene oxyamidation and amido-amidation protocol en route to accessing both isoxazoline and pyrazoline cores. Additionally, acetonitrile serves as both the solvent and an amine source in the presence of this PIDA/Lewis acid combination. This operationally straightforward and metal-free protocol provides an easy access to isoxazoline and pyrazoline derivatives.
Keywords: amido-amidation; hypervalent iodine; isoxazoline; metal-free; oxyamidation; pyrazoline

(untitled) - Kiss, L.; Nonn, M.; Fülöp, F. (Synthesis, 2012)

(untitled) - Kaur, K.; Kumar, V.; Sharma, A. K.; Gupta, G. K. (Eur. J. Med. Chem., 2014)

(untitled) - Xue, C.-B.; Wityak, J.; Sielecki, T. M.; Pinto, D. J.; Batt, D. G.; Cain, G. A.; Sworin, M.; Rockwell, A. L.; Roderick, J. J.; Wang, S.; Orwat, M. J.; Frietze, W. E.; et al. (J. Med. Chem., 1997)

(untitled) - Poutiainen, P. K.; Venäläinen, T. A.; Peräkylä, M.; Matilainen, J. M.; Väisänen, S.; Honkakoski, P.; Laatikainen, R.; Pulkkinen, J. T. (Bioorg. Med. Chem., 2010)

(untitled) - Castellano, S.; Kuck, D.; Viviano, M.; Yoo, J.; López-Vallejo, F.; Conti, P.; Tamborini, L.; Pinto, A.; Medina-Franco, J. L.; Sbardella, G. (J. Med. Chem., 2011)

(untitled) - Lee, M.; Brockway, O.; Dandavati, A.; Tzou, S.; Sjoholm, R.; Satam, V.; Westbrook, C.; Mooberry, S. L.; Zeller, M.; Babu, B.; Lee, M. (Eur. J. Med. Chem., 2011)

(untitled) - Padmavathi, V.; Thriveni, P.; Reddy, G. S.; Deepti, D. (Eur. J. Med. Chem., 2008)

(untitled) - Acharya, B. N.; Saraswat, D.; Tiwari, M.; Shrivastava, A. K.; Ghorpade, R.; Bapna, S.; Kaushik, M. P. (Eur. J. Med. Chem., 2010)

(untitled) - Dardić, D.; Lauro, G.; Bifulco, G.; Laboudie, P.; Sakhaii, P.; Bauer, A.; Vilcinskas, A.; Hammann, P. E.; Plaza, A. (J. Org. Chem., 2017)

(untitled) - Buhrlage, S. J.; Bates, C. A.; Rowe, S. P.; Minter, A. R.; Brennan, B. B.; Majmudar, C. Y.; Wemmer, D. E.; Al-Hashimi, H.; Mapp, A. K. (ACS Chem. Biol., 2009)

(untitled) - Liu, X.-H.; Ruan, B.-F.; Li, J.; Chen, F.-H.; Song, B.-A.; Zhu, H.-L.; Bhadury, P. S.; Zhao, J. (Mini-Rev. Med. Chem., 2011)

(untitled) - Kozikowski, A. P. (Acc. Chem. Res., 1984)

(untitled) - Jiang, D.; Peng, J.; Chen, Y. (Org. Lett., 2008)

(untitled) - Zhu, M.-K.; Zhao, J.-F.; Loh, T.-P. (J. Am. Chem. Soc., 2010)

(untitled) - He, Y.-T.; Li, L.-H.; Yang, Y.-F.; Wang, Y.-Q.; Luo, J.-Y.; Liu, X.-Y.; Liang, Y.-M. (Chem. Commun., 2013)

(untitled) - Han, B.; Yang, X.-L.; Fang, R.; Yu, W.; Wang, C.; Duan, X.-Y.; Liu, S. (Angew. Chem., Int. Ed., 2012)

(untitled) - Peng, X.-X.; Deng, Y.-J.; Yang, X.-L.; Zhang, L.; Yu, W.; Han, B. (Org. Lett., 2014)

(untitled) - Tripathi, C. B.; Mukherjee, S. (Angew. Chem., Int. Ed., 2013)

(untitled) - Tiecco, M.; Testaferri, L.; Bagnoli, L.; Purgatorio, V.; Temperini, A.; Marini, F.; Santi, C. (Tetrahedron: Asymmetry, 2001)

(untitled) - Dondas, H. A.; Grigg, R.; Hadjisoteriou, M.; Markandu, J.; Kennewell, P.; Thornton-Pett, M. (Tetrahedron, 2001)

(untitled) - Karapetyan, V.; Mkrtchyan, S.; Dang, T. T.; Villinger, A.; Reinke, H.; Langer, P. (Tetrahedron, 2008)

(untitled) - Mosher, M. D.; Norman, A. L.; Shurrush, K. A. (Tetrahedron Lett., 2009)

(untitled) - Zhu, L.; Yu, H.; Xu, Z.; Jiang, X.; Lin, L.; Wang, R. (Org. Lett., 2014)

(untitled) - Zhu, L.; Wang, G.; Guo, Q.; Xu, Z.; Zhang, D.; Wang, R. (Org. Lett., 2014)

(untitled) - Wei, Q.; Chen, J.-R.; Hu, X.-Q.; Yang, X.-C.; Lu, B.; Xiao, W.-J. (Org. Lett., 2015)

(untitled) - Hu, X.-Q.; Chen, J.-R.; Wei, Q.; Liu, F.-L.; Deng, Q.-H.; Beauchemin, A. M.; Xiao, W.-J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Li, W.; Jia, P.; Han, B.; Li, D.; Yu, W. (Tetrahedron, 2013)

(untitled) - Hong, K. B.; Johnston, J. N. (Org. Lett., 2014)

(untitled) - Danneman, M. W.; Hong, K. B.; Johnston, J. N. (Org. Lett., 2015)

(untitled) - Danneman, M. W.; Hong, K. B.; Johnston, J. N. (Org. Lett., 2015)

(untitled) - Reddy, B. V. S.; Reddy, N. S.; Madan, C.; Yadav, J. S. (Tetrahedron Lett., 2010)

(untitled) - Cui, H.; Liu, X.; Wei, W.; Yang, D.; He, C.; Zhang, T.; Wang, H. (J. Org. Chem., 2016)